A dual role for SAMHD1 in regulating HBV cccDNA and RT-dependent particle genesis - Wing, Peter AC; Davenne, Tamara; Wettengel, Jochen; Lai, Alvina G; Zhuang, Xiaodong; Chakraborty, Anindita; D’Arienzo, Valentina; Kramer, Catharina; Ko, Chunkyu; Harris, James M; Schreiner, Sabrina; Higgs, Martin; et al. (Life science alliance, 2019)
Chronic hepatitis B is one of the world’s unconquered diseases with more than 240 million infected subjects at risk of developing liver disease and hepatocellular carcinoma. Hepatitis B virus reverse transcribes pre-genomic RNA to relaxed circular DNA (rcDNA) that comprises the infectious particle. To establish infection of a naïve target cell, the newly imported rcDNA is repaired by host enzymes to generate covalently closed circular DNA (cccDNA), which forms the transcriptional template for viral replication. SAMHD1 is a component of the innate immune system that regulates deoxyribonucleoside triphosphate levels required for host and viral DNA synthesis. Here, we show a positive role for SAMHD1 in regulating cccDNA formation, where KO of SAMHD1 significantly reduces cccDNA levels that was reversed by expressing wild-type but not a mutated SAMHD1 lacking the nuclear localization signal. The limited pool of cccDNA in infected Samhd1 KO cells is transcriptionally active, and we observed a 10-fold increase in newly synthesized rcDNA-containing particles, demonstrating a dual role for SAMHD1 to both facilitate cccDNA genesis and to restrict reverse transcriptase-dependent particle genesis.